Розробка компонентів інформаційної системи меблевої компанії - Сердюк, П. О. (ХНУРЕ, 2024)
During this work, an information system was developed for the furniture center. It is designed to store, search and process information about about products, customers, orders, expenses, and profits. This information system allows each user to view the catalog of available furniture and find out detailed information about each item. The system provides the following roles for access to the system: unregistered user, client, and administrator. Each of them has different access levels. The site has a minimalist design and contains only relevant information so that all users can easily find what they are interested in. what they are interested in. The use of modern technologies will automate the processes of providing information, ordering, and reporting.
Keywords: база даних меблів; система замовлень; управління запасами